Increased risk of portal vein thrombosis in patients with autoimmune hepatitis on the liver transplantation waiting list. Issue 7 (11th June 2017) - Ruiz, Pablo; Sastre, Lydia; Crespo, Gonzalo; Blasi, Annabel; Colmenero, Jordi; García‐Valdecasas, Juan Carlos; Navasa, Miquel
Abstract: Liver transplantation (LT) is indicated in autoimmune hepatitis (AIH) for both acute presentation with liver failure and end‐stage chronic liver disease. Few studies have suggested an association between AIH and coagulation disorders and a higher incidence of portal vein thrombosis (PVT) in patients with AIH listed for LT. The aim of this study was to determine the incidence of thrombotic complications, particularly PVT, in a cohort of 37 patients undergoing LT because of AIH. PVT was present before transplantation in 30% (n=11) of these patients compared to 11% in the whole population transplanted in our center ( P =.002). On comparing only patients with cirrhosis, PVT was present in 55% of the AIH group, being 12% in the whole cohort ( P <.001). Among patients with PVT before LT, no patient receiving anticoagulation therapy early after LT developed recurrence of PVT, whereas two patients (33%) without anticoagulation therapy did. The increased incidence of PVT in the pretransplant period and the possibility of thrombosis recurrence after LT suggest that patients with AIH and PVT could benefit from anticoagulation therapy after transplantation. However, further studies are needed to recommend anticoagulation in these patients in clinical practice.